Synthesis, Characterization and Antimicrobial Activity of Transition Metal Complexes of [NN] Donor Benzenesulfonamide Based Schiff Bases - Athar, Ali; Batool, Wajeha; Ullah, Farman; Haq, Zia ul; Ullah, Malik Aman; Ahmed, Fawad; Khurram, Jahazeb (Asian Journal of Chemistry, 2017)
The new sulfonamide Schiff based ligands have been prepared by refluxing 7-methylquinoline-3-carbaldehyde and halo derivatives of benzenesulfonamide in methanol for 4-6 h. The complexes of Cu, Co, Ni and Zn have been synthesized and characterized on the basis of their physical characteristics, micro-analytical data, 1H NMR, FT-IR spectrum and electronic spectrum data. The FT-IR spectrum data suggest that Schiff base ligand behaves in bidentate manner as coordinated with transition metals through nitrogen of azomethine group and nitrogen of quinolone group. 1H NMR data confirm formation of the metal complexes. Biological screening effect of Schiff bases and their metal complexes have been studied against Gram-positive and Gram-negative bacteria by disc diffusion technique. The electronic spectrum data confirm the octahedral geometry of the complexes. Biological activities show that the metal complexes synthesized complexes exhibit higher antibacterial activity than that of Schiff base against tested bacteria.